Improving Tobacco Besuki Na-Oogst Competitiveness: Does Tobacco Still at a Crossroads? - Adhitya Wardhono; Josi Ali Arifandi; Yulia Indrawati; M Abd. Nasir; Ciplis Gema Qori'ah (Soegijapranata Catholic University, 2021)
Tobacco Besuki Na-Oogst (BesNO) is a fancy product and becomes a leading export-oriented commodity, especially as a raw material for making cigar. The embarrassment of Besuki Na-Oogst is a plant which has location specifics. Every tobacco-producing region has distinctive qualities. Tobacco Besuki Na-Oogst (BesNO) quality is measured using standards that are easily implemented by all tobacco Besuki Na-Oogst business actors. The research objective is to determine the competitiveness of tobacco Besuki Na-Oogst as an export quality product. The analytical method used is descriptive analysis and SWOT. The research took place in Jember Regency Indonesia. The results show that tobacco Besuki Na-Oogst's strategic potential is supported by supporting infrastructure capacity in testing tobacco quality, geographical potential and human resources in the face of competition and international policy. The strategy applied is to support aggressive growth policies through improving the quality of cultivation and capacity of standard infrastructure and the quality and quality of human resources in the face of international competitiveness.